The Development of Local Debt Markets in Asia - Goswami, Mangal (IMF Working Papers; Working Paper ;, 2011)
The paper makes an assessment of the progress made in developing local debt markets in emerging Asia. Market development has been limited by hurdles confronting borrowers and lenders, current and potential liquidity providers, and insufficient support from government policies and regulations. Besides fostering a credit culture to deepen local debt markets, the issue of critical size can be addressed through an integrated regional market for local currency bonds that provides greater scale, efficiency, and access. With rapid economic growth in Asia, a key challenge is to generate financial assets that can provide the underlying collateral for expanding fixed-income markets, and hence domestic and regional investment opportunities.